2019
DOI: 10.1136/bmjpo-2019-000435
|View full text |Cite
|
Sign up to set email alerts
|

Mild to moderate hypersensitivity reactions to beta-lactams in children: a single-centre retrospective review

Abstract: ObjectiveBeta-lactam (BL) antibiotics are the most reported drugs in hypersensitivity reactions in children. More than 90% of these children tolerate the suspected drug after diagnostic work-up. Skin tests (STs) show low sensitivity. Our aim was to assess the performance of drug provocation tests (DPTs) without previous ST in mild and moderate delayed reactions and to propose a new DPT protocol.Design of the studyCharts from 213 children under 15 years of age referred for suspected BL allergy from 2011 to 1013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…In studies that performed prolonged DPT, a rate of positive results ranging from 2% to 17.2% was found. Because such rate was >10% in several studies, it has been suggested that prolonged DPT increase the allergy workup sensitivity in nonimmediate reactors to BL.…”
Section: Diagnosismentioning
confidence: 99%
See 4 more Smart Citations
“…In studies that performed prolonged DPT, a rate of positive results ranging from 2% to 17.2% was found. Because such rate was >10% in several studies, it has been suggested that prolonged DPT increase the allergy workup sensitivity in nonimmediate reactors to BL.…”
Section: Diagnosismentioning
confidence: 99%
“…DPT have been recommended by both the European guidelines 22,30,31,67,68 and the US practice parameter 35 as a part of the BL allergy workup. However, only the European guidelines 22,30,31,67,68 emphasized their role in the establishment of a firm diagnosis of During the last decade, DPT with the suspected BL have been performed in series larger than 100 subjects involving either pediatric [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] or adult 29,58,[87][88][89][90][91][92][93][94][95][96][97][98][99] populations or both, 18,100-109 highly enhancing our knowledge on the usefulness and safety of this diagnostic tool in BL allergy workup. This knowledge has contributed to achieving agreement on several areas of the general principles for DPT (high/strong) ( Table 5).…”
Section: Drug Provocation Testsmentioning
confidence: 99%
See 3 more Smart Citations